Wybrane wyzwania prawne i organizacyjne związane z wdrażaniem systemów AI w działalności samorządów terytorialnych - Szpyt, Kamil; Bilski, Artur (PRAWO i WIĘŹ, 2025)
The paper examines the challenges of implementing artificial intelligence (AI) systems in local government units (LGUs). The authors discuss key legal and organizational issues, focusing on the potential benefits and risks of implementing AI systems. Particular attention is paid to the AI Act, its impact on LGU’s operations, and challenges such as data protection and high implementation costs. The authors emphasize that artificial intelligence has the potential to revolutionize TSU operations but requires adequate preparation, resources and a legislative framework.